Alzheimer’s Disease and Risk of Hip Fracture: A Meta-Analysis Study - Yan Zhao; Liang Shen; Hong-Fang Ji (The Scientific World Journal)
Background. Alzheimer's disease (AD) is the most common cause of dementia in the elderly population. Growing evidence supports that AD patients are at high risk for hip fracture, but the issue remains questionable. The purpose of the present study is to perform a meta-analysis to explore the association between AD and risk of hip fracture. Considering that bone mineral density (BMD) acts as a strong predictor of bone fracture, we also studied the hip BMD in AD patients. Methods. We searched all publications in Medline, SciVerse Scopus, and Cochrane Library published up to January 2012 about the association between AD and hip fracture or hip BMD. Results. There are 9 studies included in the meta-analysis. The results indicate that AD patients are at higher risk for hip fracture (OR and 95% CI fixed: ES = 2.58, 95% CI = [2.03, 3.14]; dichotomous data: summary OR = 1.80, 95% CI = [1.54, 2.11]) than healthy controls. Further meta-analysis showed that AD patients have a lower hip BMD (summary SMD = −1.12, 95% CI = [−1.34, −0.90]) than healthy controls. Conclusions. It was found that in comparison with healthy controls AD patients are at higher risk for hip fracture and have lower hip BMD.